2014
DOI: 10.3758/s13421-014-0422-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility within working memory and the focus of attention for sequential verbal information does not depend on active maintenance

Abstract: The focus of attention seems to be a static element within working memory when verbal information is serially presented, unless additional time is available for processing or active maintenance. Experiment 1 manipulated the reward associated with early and medial list positions in a probe recognition paradigm and found evidence that these nonterminal list positions could be retrieved faster and more accurately if participants were appropriately motivated-without additional time for processing or active mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 64 publications
12
43
2
Order By: Relevance
“…The current results are consistent with the existence of a flexible 1-item focus of attention in WM, with the item represented in the focus of attention having a special status (e.g., Oberauer, 2002;Sandry, Schwark, & MacDonald, 2014). When it comes to the specific nature of this special status, we observe a clearly positive effect on the accessibility of the item in the focus of attention, whereas Johnson et al (2013) observed a negative effect on the Refreshing in WM 29 accessibility of the item in the focus of attention.…”
Section: Heightened-accessibility Of the Just-refreshed Memory Itemsupporting
confidence: 77%
“…The current results are consistent with the existence of a flexible 1-item focus of attention in WM, with the item represented in the focus of attention having a special status (e.g., Oberauer, 2002;Sandry, Schwark, & MacDonald, 2014). When it comes to the specific nature of this special status, we observe a clearly positive effect on the accessibility of the item in the focus of attention, whereas Johnson et al (2013) observed a negative effect on the Refreshing in WM 29 accessibility of the item in the focus of attention.…”
Section: Heightened-accessibility Of the Just-refreshed Memory Itemsupporting
confidence: 77%
“…In the visual domain, such effects are typically observed even though participants are asked to concurrently articulate irrelevant verbal information during presentation and maintenance (e.g., Atkinson et al, 2018;Hu et al, 2014;2016;Hitch et al, 2018), and are therefore unlikely to critically involve verbal rehearsal. Similarly, Sandry et al (2014) observed that prioritization effects for visually presented verbal material remained intact under a similar form of articulatory suppression. However, it is unclear whether the same applies when to-be-remembered information is aurally encountered, with no corresponding visual component to the task.…”
Section: Methodsmentioning
confidence: 80%
“…This task disrupts an individual's ability to rehearse (Baddeley, 1986;Camos et al, 2009). Enhanced short-term and long-term memory performance was observed for high value items, suggesting that individuals can indeed direct attention to more valuable verbal information (Sandry et al, 2014;. The presence of these effects under articulatory suppression also indicates that prioritization effects are not reliant on verbal rehearsal.…”
mentioning
confidence: 99%
“…We see refreshing as an increase in the accessibility of a representation after it enters the focus of attention that remains after the focus moves away . If this was not the case, refreshing could only benefit one item at a time, instead of yielding a cumulative benefit.…”
Section: Refreshing As a Cumulative Focusing Benefitmentioning
confidence: 95%